Synthesis of 3,4-fused y-lactone-y-lactam and y-lactonepyrrolidine bicyclic systems / Nur Aini Azib - Azib, Nur Aini (Institute of Graduate Studies, UiTM, 2018)
In this study, bicyclic moieties 3,4-fused y-lactone-y-lactam and y-lactone-pyrrolidine were chosen as the target molecules due to their highly functionalized structures and their ability to be bioactive 5,5-bicyclic molecules. The synthetic strategy was divided into three main parts in which the first part concentrated on the construction of the key-intermediates, lactam and pyrrolidine ring moieties, from D-alanine methyl ester hydrochloride. The approach involved N-protection of the starting material with either benzyl or Boc protecting groups. Condensation with methyl malonyl chloride followed by Dieckmann cyclization gave the required y-lactam ring moiety 5 which is also known as the p,pdiketoester with an overall yield of 39%. Consequently, decarboxylation of the methyl ester functional group followed by reduction of the keto amide functionality with LiAlH4 afforded the desired pyrrolidine ring 25 in 18% overall yield. The second part focused on the formation of the fused y-lactone-y-lactam and y-lactone-pyrrolidine bicyclic systems. The y-lactam ring moiety underwent C-alkylation reaction at the C3-position via insertion of the ethyl acetyl functionality by utilizing TBAF as the base. Subsequently, selective dimethoxy-carbonylation was performed using two different decarboxylating agents which were a salt-solvent system, Lil/DMF, and an acid medium, HCl/AcOH; both successfully gave decarboxylated products but the former with the presence of C-3 methyl group as anticipated and the latter without…